Ergonomic implementation of movement interventions in healthcare from the point of view of the physiotherapist - David Ravnik; Katerina Merše Lovrinčević; Václav Bittner (Karolinum Press, 2024)
Introduction: Healthcare workers have a high prevalence of musculoskeletal problems, which are often associated with the physical demands of their work, especially with manual handling, lifting and helping patients with mobility. In this paper, we examined these interventions from the physiotherapist's point of view, mainly with the help of biomechanics, and proposed appropriate ergonomic approaches to reduce risks of musculoskeletal disorders. Methods: We analysed two basic interventions: helping patients to sit over the edge of the bed (starting in the supine position) and helping them to stand up. To determine the safest and most effective methods, we used a combined approach of biomechanics and ergonomics, and we also considered the patient's cooperation in order to train independence and functionality. This approach has also been explained with the help of ergonomic principles. Results: The optimization of assisting patients to sit over the edge of the bed emphasized minimal lifting, gradual execution, effective rotation of partial centres of gravity, patient activation, use of levers (to use gravity), and rotation instead of lifting. When helping patients to stand up, it is most optimal for the healthcare worker to stand next to the patient, ideally on the side where the patient has preserved better functionality. All the proposed methods have proven to be more ergonomically effective and safe, and allow the patient to gain more independence and functionality. Discussion: By incorporating the principles of ergonomics and biomechanics, we can reduce the physical burdens of healthcare workers, which does not only improve the safety of healthcare providers, but also increases the safety and independence of patients. Our findings highlight the need to evaluate the relevance of traditional approaches to lifting and handling patients in healthcare. Conclusion: Incorporation of optimized methods into patient mobility curricula for healthcare professionals is suggested. Policy changes that focus on reducing manual tasks and lifting and include ergonomic interventions can play a key role in reducing work-related musculoskeletal problems.